(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Development of technical thinking and creative attitude to work is one of the most important tasks of educating a new person. For this purpose, in the research work, the future technology teacher, technical creativity will arise as a result of our scientific research on the methods of formation of construction knowledge, skills and skills and the use of computers in the construction process. The modern world level of the development of information and communication technologies is such that the creation of a national system compatible with the integration of the infrastructures of the world information space and the national information and computing network in the republic is an important factor in the effectiveness of the national economy, management, science and education. These problems are very complex and at the same time urgent for our republic. The results of the implementation of economic, structural and other changes currently being carried out depend on how and in what time frame the problems related to informatization are solved in the republic. The creation of electronic educational tools for educational subjects further expands the possibility of using modern information and communication technologies in teaching these subjects. This, in turn, is the main factor of students’ in-depth assimilation of knowledge in these subjects and increases the quality and efficiency of education. The implementation of such efforts will further accelerate the wide application of modern pedagogical and information technologies in the educational process, equip professors and teachers with advanced pedagogical knowledge and technologies, improve their skills, and use the experience of foreign higher education institutions. provides an opportunity for in-depth study and introduction of their effective methods and tools into our national education system